KEPALSUAN HUKUM DALAM PENANGANAN KORUPSI DI INDONESIA PADA MASA PEMERINTAHAN SUSILO BAMBANG YUDHOYONO - Rina Khairani Pancaningrum (FAKULTAS HUKUM UM PAREPARE, 2017)
False Law in the handling of Corruption in Indonesia in the era of Susilo Bambang Yudhoyono describes the law enforcement conditions that have not been maximized so as to reduce public confidence in the government's performance at that time, this journal aims to know the picture of handling corruption in the era of Susilo Bambang Yudhoyono; This journal uses the normative juridical method. While the analysis with qualitative methods. The result of this paper is the condition of keos which is caused by the falsity of law in handling corruption in Indonesia in the era of Susilo Bambang Yudhoyono government, is not something to be feared or avoided or resisted by antipathy. But the first and most important step to build public trust is to